The effect of renin-angiotensin-aldosterone blockers on SARS-CoV-2 infection in adults: a systematic review of studies and meta-analyzes - М. V. Leonova (Медицинский совет, 2021)
The article discusses the role of immune dysregulation of the renin-angiotensin-aldosterone system (RAAS) in the pathogenesis of COVID-19 infection, the participation of ACE2 for the penetration of the SARS-CoV-2 coronavirus into cells and the possible role of RAAS blockers, which have a direct effect on the pathological activity of the RAAS, in the development of and the severity of the disease. It is noted that the beneficial organoprotective effects of ACE inhibitors and ARBs may protect against SARS-CoV-2 infection, and their withdrawal may lead to clinical decompensation in patients at high risk of cardiovascular risk. Since then, a number of observational cohort studies have been carried out to address the main questions: does the use of an ACE inhibitor or ARB increase the risk of contracting the novel SARS-CoV-2 coronavirus, and whether the use of RAAS blockers is associated with worse outcomes of COVID-19 disease. The article provides an overview of the scientific evidence on the relationship between the use of RASS blockers and COVID-19 infection. Several cohort studies and two meta-analyzes found no association between prior use of an ACE inhibitor/ARB and the risk of COVID-19 infection (RR 0.96–0.99). In studies on the study of clinical and laboratory features of the action of RAAS blockers in COVID-19, a significantly larger number of subpopulations of T-lymphocytes CD3+ and CD8+, lower concentrations of biomarkers (C-reactive protein, ferritin, IL-6, procalcitonin), as well as a lower viral load. In clinical outcomes, with the use of an ACE inhibitor/ARB, there was a lower incidence of severe/critical forms, and a shorter duration of hospitalization. In large cohort studies with >1000 patients, the use of an ACE inhibitor/ARB was not associated with an increase in the risk of death in patients with COVID-19 (RR < 1.0), and some studies showed a 37–67% decrease in RR. Meta-analyzes also confirmed the absence of the effect of RAAS blockers on the risk of mortality, and in the population of patients with hypertension, a significant reduction in the risk of mortality and severe course of COVID-19 was revealed. Most international associations of specialists, as well as the Russian Cardiological Society, are recommended to continue the use of RAAS blockers in patients with cardiovascular diseases and not to be canceled in case of COVID-19 disease. Further randomized clinical trials are needed to generate new evidence.